One‐Way Water‐Transport Cotton Fabrics with Enhanced Cooling Effect. Issue 17 (29th June 2016) - Zhou, Hua; Wang, Hongxia; Niu, Haitao; Zeng, Chao; Zhao, Yan; Xu, Zhiguang; Fu, Sida; Lin, Tong
Abstract : Two types of directional water transport fabrics are prepared by using cotton fabric as substrate and an electrospraying technique to apply a hydrophobic coating on one side of the fabric. The main difference between the two electrosprayed fabrics is that one of them was precoated with a hydrophilic thermoconductive resin over the fiber surface prior to electrospraying. As a result, the precoated fabric has a much higher thermoconductivity than the other, while they are similar in water transport and fibrous structure. In the wet state, the directional water‐transport fabrics generate a temperature difference between the two fabric sides while drying naturally. The fabric with higher thermal conductivity shows smaller temperature difference, better thermal transfer within the fabric, stronger evaporation cooling effect, and accelerated moisture evaporation. Directional water transport fabrics with high thermal conductivity may be used to mitigate thermal burden in sportswear, summer clothing, medical fabrics, and workwear. Abstract : A one‐way water transport cotton fabric with an enhanced evaporation cooling effect is prepared by dip‐coating a boron nitride‐containing resin throughout the fabric and subsequently electrospraying one side to make this side hydrophobic.